Religious Values and Multiculturalism in the Sayyang Pattu'du Tradition in West Sulawesi Indonesia - Ikhlima Yaumil Fitri Bansu; Nourelhuda S. B. Elmanaya; Mohamed Gamal Ibrahim ElBasiouny; Muthoifin; Sudarno Shobron (Walidem Institute and Publishing (WIP), 2023)
The value of religious character is very important in efforts to develop the human resources of a nation. The value of religious character can be extracted from cultural treasures that are in line with the characteristics of the local community, including the value of religious character which can be explored in the sayyang pattu'du tradition in Polewali Mandar. This study aims to determine: 1) the process of implementing the sayyang pattu'du tradition in Polewali Mandar, and 2) the values ​​of religious character contained in the sayyang pattu'du tradition in Polewali Mandar. This research paradigm is qualitative with the type of field research and a phenomenological approach. The data collection process was carried out by observation, interviews, and documentation. The data analysis includes data reduction, data presentation, and conclusion. The result of this research is Sayyang Pattu'du which means a dancing horse or animal which is taught with dancing movements. This tradition is a form of appreciation from parents to their children when they have learned the Qur'an, namely parading children around the village on horseback. This tradition is carried out once a year. Children who ride horses wear traditional Mandar clothes and before they get on the horse they have to bow to their Qur’an teacher, as a form of respect. The route of the procession starts from the mosque and then continues around the village, in a situation like this the dancing horse (sayyang pattu'du) constantly displays its skill in dancing to the tambourine interlocking rhythm. The values ​​of character religion contained in the sayyang pattu'du tradition are 1) Islamic religion.